New Hair Growth Cream Formulation with Cocoa Pod Peel (Theobroma cacao L.) - Resmi Mustarichie; Aliya Nur Hasanah; Gofarana Wilar; Dolih Gozali; Nyi Mekar Saptarini (The Scientific World Journal)
Our previous study verified that the waste skin of cocoa (Theobroma cacao L) fruit or waste cocoa pod husks had the efficacy to overcome hair loss or alopecia. This study aims to determine the formula and activity of hair cream of cocoa pod peel water fraction, which is effective in stimulating hair growth. Activity testing uses the modified Tanaka method. The results showed that the cocoa husk wastewater fraction could be formulated into hair cream, but there were changes in viscosity and pH after the freeze-thaw test, but still within the allowed limit. The hair cream water fraction gel stimulated hair growth activity based on the hair length data with a significant difference in concentration of the preparation. The best activity in hair cream preparation was at 12.5% concentration. In addition, there were no signs of irritation to the rabbit’s skin where hair cream preparation was applied. The results of this study indicated that cocoa fruit peel cream can be used for antialopecia treatments.